The influence of principal’s strategies and teachers’ professional competency toward education quality - Tin Nuryanti; Happy Fitria; Missriani Missriani (Journal of Educational and Learning Studies, 2021)
This study aims to analyze the influence of the principal’s strategy and teacher professional competence on the quality of education in SMP Negeri 13 Palembang.Respondents in this study were all teachers in school which amounted to 53 people. The details of this study sample were 43 respondents with ASN status and 10 respondents with honorary status by using quantitative methods.The results of this study were obtained that first there is a significant influence of the principal's strategy variables on the quality of education. The principal’s improving strategy has a positive impact on the quality of education which will also. Second, there is a significant influence of teacher professionalism variables on the quality of education. The professionalism of teachers who are getting better has a positive impact on the quality of education that will also be better.. Third, there isa significant influence of the principal's strategic variables and professionalism on the quality of education. The variables of the principal's strategy and the professionalism of teachers were able to affect the quality of education by 77.4%.